The elusive quest for growth in Argentina - Chudnovsky, Daniel (Palgrave Macmillan, 2007)
Despite its unusually rich availability of natural resources and ample base of human capital, in the last forty years Argentina suffered a poor growth performance in any cross-country comparison. Chudnovsky and L̤pez's analysis includes two episodes of growth in 1964-74 and in 1991-98 that proved to be finally unsustainable, as well as the 2001 crisis, the most severe in the country's history. Since both growth episodes took place under quite different development paradigms, the Post-War Development Consensus and Washington Consensus, lessons about what went right and wrong in Argentina contributes to the debate about the virtues and failures of those paradigms. Following mainly an institutional and historical approach, but also employing rigorous economic analysis, this book offers a timely contribution to one of the big puzzles in the field of development economics.